Kepuasan Sharing Knowledge Teknik Early Warning Pencegahan Black SEO dalam Website Pemerintah Daerah - Prasetyo, Heri; Harjito, Bambang; Sihwi, Sari Widya; Winarno, Winarno; Wiranto, Wiranto (Universitas Ekuitas Indonesia, 2024)
The increased number of internet users in Indonesia has also spurred the usage of search engines. With so many search engine users, Search Engine Optimizer (SEO) arose. However, alongside the rapid rise of SEO, hackers emerged. These hackers utilize government websites for malicious commercial purposes. This type of marketing is known as